2016
DOI: 10.1007/s00107-016-1071-9
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of rubberwood (Hevea brasiliensis) treated with chitosan or silane against surface molds

Abstract: The aim of this study was to determine the efficacy of chitosan and methoxysilane in the prevention of surface mold growth on rubberwood. Three different chitosan samples were tested; C1 (Mw 37 kDa), C2 (Mw 5.4 kDa) and C3 (Mw 3.5 kDa). Radial growth inhibition assay of the chitosan samples was investigated at concentrations ranging from 0.063 to 0.5 %w/v against Aspergillus niger BAM 4 and Penicillium decumbens CBS 121928. Chitosan samples C1 and C3 exhibited strong antifungal activity against both molds. Rub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…According to literature data, wood impregnated with alkoxysilanes shows no resistance to moulds, such as Alternaria alternata , Cladosporium herbarum , A. niger , Penicillium decumbenes and Penicillium brevicompactum [ 50 , 52 , 53 , 54 ]. In turn, Ghosh et al [ 55 ] reported that impregnation with an amino-silicone macro-emulsion resulted in a certain resistance to growth of moulds (including A. versicolor , Ulocladium strum and Aureobasidium pullulans ) on wood surfaces, whereas wood treated with the same concentrations of silicone quat micro-emulsion and alkyl-modified silicone macro-emulsion exhibited comparatively lower resistance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to literature data, wood impregnated with alkoxysilanes shows no resistance to moulds, such as Alternaria alternata , Cladosporium herbarum , A. niger , Penicillium decumbenes and Penicillium brevicompactum [ 50 , 52 , 53 , 54 ]. In turn, Ghosh et al [ 55 ] reported that impregnation with an amino-silicone macro-emulsion resulted in a certain resistance to growth of moulds (including A. versicolor , Ulocladium strum and Aureobasidium pullulans ) on wood surfaces, whereas wood treated with the same concentrations of silicone quat micro-emulsion and alkyl-modified silicone macro-emulsion exhibited comparatively lower resistance.…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of silicon (coming from organosilane compounds) in wood impregnated with silanes and the propolis-silane formulations determined by flame atomic absorption spectrometry is presented in Table 2. Analysis of Si concentration in wood samples treated with silicon compounds is a useful tool in assessment their presence in wood structure [36,49,50]. The silicon concentrations in treated wood indicated that wood samples impregnated with both silane-propolis formulations contained higher amounts of Si compared to wood treated with silicon compounds without the propolis extract.…”
Section: Atomic Absorption Spectrometrymentioning
confidence: 99%
“…Chitosan is the most frequently studied polymer of animal origin as a component of wood preservatives. The literature data report that the antifungal activity of chitosan as a wood preservative depends on its concentration, molecular weight, the solvent used for the chitosan dissolved, or fungal strain [ 21 , 90 , 153 , 154 , 155 , 156 ]. The increase in chitosan concentration and molecular weight increases its fungicidal activity [ 21 , 154 ].…”
Section: Animal-derived Antifungal Agentsmentioning
confidence: 99%
“…Among the three different chitosan samples, two chitosan dissolved in weak acid solutions showed strong antifungal activity against A. niger and Penicillium decumbens , while chitosan in the form of an aqueous oligomer solution exhibited a 100% reduction in the colony size only against P. decumbens in the radial growth inhibitor assay. On the other hand, rubberwood ( Hevea brasiliensis ) treated with an acid chitosan solution showed resistance against A. niger , and no resistance against P. decumbens [ 153 ]. Wood samples impregnated with 5% chitosan solution showed resistance against the brown rot fungi C. puteana , T. versicolor , and P. placenta , while wood treated with a lower concentration of chitosan exhibited no resistance to the tested fungi [ 21 , 157 ].…”
Section: Animal-derived Antifungal Agentsmentioning
confidence: 99%
“…The literature data showed that chitosan limited the growth of decay fungi (C. puteana, P. placenta and T. versicolor); however, the mass loss of treated wood was related to chitosan concentration, strain of fungi and molecular weight of chitosan (Alfredsen et al 2004;Eikenes et al 2005). The molecular size of chitosan and its concentration also impact the anti-mold properties of chitosan-treated wood (Gorgij et al 2014;El-Gamal et al 2016;Oldertrøen et al 2017). Chitosan was also applied to wood treatment in combination with other substances, including cinnamaldehyde, polyethylene glycol, propolis extract and silver nanoparticles (Silva-Castro et al 2018;Casado-Sanz et al 2019;Bi et al 2021;Fang et al 2021).…”
Section: Introductionmentioning
confidence: 99%